THE MODEL OF COMPETITIVE ADVANTAGE FOR JAVA BATIK MSES - Anwar Sulaiman; Ruwaida Ruwaida; Rufial Rufial (Dinasti Publisher, 2020)
The purpose of this study was to determine and analyze the effect of entrepreneurial orientation, marketing capabilities, market orientation, and technological innovation partially or collectively on competitive advantage. To find out and analyze the effect of entrepreneurial orientation, marketing capabilities, market orientation, and technological innovation on competitive advantage either partially or collectively. The population in this study amounted to 330 MSEs Batik entrepreneurs in Central Java, divided into 2 cities and 3 districts, namely the city of Surakarta and the city of Pekalongan, as well as Sragen, Sukoharjo, and Pekalongan districts. The research method used in this research is quantitative research methods. The research design used explanatory research and descriptive research through survey and questionnaire approaches. The analysis used in this research is the Confirmatory Factor Analysis (CFA). The statistical analysis tool used was LISREL 8.70. Based on the research results, the following research findings are as follows entrepreneurial orientation, marketing capability, market orientation, and technological innovation partially or collectively have a positive and significant effect on competitive advantage. Technological innovation is partially the variable with the greatest contribution value to competitive advantage. Based on the research results, the following research findings are as follows entrepreneurial orientation, marketing capability, market orientation, and technological innovation partially or collectively have a positive and significant effect on competitive advantage. Technological innovation is partially the variable with the greatest contribution value to competitive advantage. Based on the research results, the following research findings are as follows entrepreneurial orientation, marketing capability, market orientation, and technological innovation partially or jointly have a positive and significant effect on competitive advantage. Technological innovation is partially the variable with the greatest contribution value to competitive advantage.